Дія больового стресу на поведінкові реакції у тварин із різним профілем моторної асиметрії - Горна, Оксана; Станішевська, Тетяна; Gorna, Oksana; Stanishevska, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2016)
Вивчено варіабельність больової чутливості в щурів із різним профілем моторної асиметрії при експери-ментально викликаному тонічному болі у «формаліновому тесті». Показано, що коефіцієнт моторної асиметрії тварин може слугувати критерієм їхньої чутливості до больового стресу. The variability of pain sensitiveness of rats with different type of motor asymmetry at the experimentally caused tonic pain in a «formalin test» has been studied. Changes of animals’ behavioral reactions continuality under the condition of sharp pain stress depend on individual-typological peculiarities of motor asymmetry. The most sensitive to pain stress appeared to be the rats with left-side motor lateralization, i.e. with the dominant right hemisphere of the brain, and the least – with the dominant left hemisphere («right-handed rats») and with the unexpressed functional asymmetry («ambidextrous rats»). So, differences found in the pattern of behavioral reactions of animals of various individual-typological groups prove that the type of motor asymmetry of animals can serve as a criterion of their sensitiveness to pain stress influence.
Pain Stress Influence on Behavioral Reactions of Animals with Different Type of Motor Asymmetry
Keywords: больова чутливість; коефіцієнт моторної асиметрії; формаліновий тест; поведінкові реакції; pain sensitiveness; coefficient of motor asymmetry; formalin test; behavioral reactions